Deep targeted sequencing of cytological tumor cells using whole genome amplification. Issue 1 (11th October 2022) - Amemiya, Kenji; Hirotsu, Yosuke; Mochizuki, Hitoshi; Higuchi, Rumi; Nakagomi, Takahiro; Goto, Taichiro; Oyama, Toshio; Kondo, Tetsuo; Omata, Masao
Abstract: Background: Genomic profiling in lung cancer is essential for precision medicine. Cytological specimens provide an alternative to formalin‐fixed paraffin‐embedded (FFPE) samples for comprehensive genomic analysis. However, this approach remains challenging when a limited number of tumor cells are available. We applied whole genome amplification (WGA) to cytology specimens to overcome this limitation. Methods: Using a lung cancer panel targeting 58 genes, we performed next‐generation sequencing of whole genome‐amplified DNA extracted from cytological specimens containing 10–20 tumor cells (cyto‐WGA) and DNA from corresponding FFPE tumor tissue. We compared sequencing data from cyto‐WGA and FFPE samples to examine the detection accuracy of copy number variations and oncogenic and drug‐matched variants. Results: The DNA quality and quantity from cyto‐WGA were higher than those from FFPE samples ( p < .0005 and p < .05, respectively). Sequencing metrics of cyto‐WGA and FFPE tissues showed no difference in the number of mapped reads and mean coverage depth, but there were significant differences in the on‐target rate ( p < .05) and uniformity ( p < .0005). Copy number variations in cyto‐WGA samples ( n = 211) were higher than in FFPE samples ( n = 9) ( p < .0001). Fourty nine oncogenic variants were detected in cyto‐WGA and 39 in FFPE. Of these variants, 34 (63%) were present in both samples. In addition, all 16 drug‐matched variants were detected in FFPE and cyto‐WGA samples with 100% concordance. Conclusion: Cyto‐WGA can be a feasible and alternative method to detect oncogenic and drug‐matched variants. Abstract : The authors compared sequencing data from cytological whole genome amplification (WGA) and formalin‐fixed paraffin‐embedded samples to examine the detection accuracy of copy number variations and oncogenic and drug‐matched variants. Cytological WGA can be a feasible and alternative method to detect oncogenic and drug‐matched variants.